Early Survival of Comatose Patients after Severe Traumatic Brain Injury with the Dual Cannabinoid CB1/CB2 Receptor Agonist KN38-7271: A Randomized, Double-Blind, Placebo-Controlled Phase II Trial - Firsching, Raimund; Piek, Jürgen; Skalej, Martin; Rohde, Veit; Schmidt, Uwe; Striggow, Frank; null (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2012)
Background and Study Object Despite many drug trials, no substance has yet been identified that improves the outcome of severe head injury. The dual cannabinoid CB1/CB2 receptor agonist KN38-7271 mediates potent neuroprotection in animal models. We describe here the first randomized, double-blind, prospective, placebo-controlled clinical phase IIa proof-of-concept trial to investigate the safety, pharmacokinetics, and potential efficacy of a cannabinoid receptor agonist in humans.Patients and Methods Out of the 439, 97 comatose patients at 14 European neurosurgical centers met the inclusion criteria. KN38-7271 was administered within 4.5 hours of the injury, and the patients received 1000, 500 μg, or placebo. The primary analysis was pharmacokinetic; efficacy was measured by survival and by neurological improvement or deterioration 7 and 14 days and 1, 3, and 6 months after the injury. Intracranial pressure (ICP) and cerebral perfusion pressure (CPP) were analyzed from start of treatment to end of day 7.Results Survival rates within 1 month of the injury were significantly better in the treatment groups than in the placebo group (high-dose, Kaplan–Meier difference on day 30 + 0.12 with p = 0.043; low-dose, difference +0.15 with p = 0.011) but this effect was not seen after 6 months. Critical ICP and CPP were less extreme and less frequent in the treatment group. There were no severe and no serious adverse effects that could be attributed to KN38-7271.Conclusions KN38-7271 appeared beneficial in the acute early phase of the comatose patient after a head injury. Its use was safe and well tolerated by patients. These results may provide the basis for further phase II/III trials in larger study populations.
Keywords: traumatic brain injury; severe head trauma; cannabinoids; cannabinoid receptor agonist